Soil moisture retention and mass movement of volcanic soils from the “Sabinas” sector in Caldas, Colombia (2017)
The mass movement of soils, are soil, rocks displacements or both, caused by soil water excesses in terrains due to gravity effects and other factors. The aim of this research was to quantify the moisture retention capacity of volcanic soils as a threat indicator in the mass removal phenomena. This research was carried out on soils of the Malteria - Las Margaritas road transept to Magdalena river, right bank of the Chinchiná river in the Department of Caldas, Colombia. Through soil sample design, 3 altitudinal ranges were stratified as follows: high, medium and low. In fact, representative plant cover was taken in the study area, sampling the combination of the following variables: "plant cover" and "altitudinal range". In total, 52 points were sampled and georreferenced. High moisture retention was confirmed with saturation levels at different stresses as fundamental triggers of the phenomenon as a consequence of the soil aggregates instability to soil moisture, high porosity and high hydraulic conductivity and its relation with the mineralogy of these soils, high rainfall regimes of the region, altitudinal position, terrain slopes, which determine the relative threat by mass movement of soils. Intervariable correlations were found to facilitate the explanation of the mass removal of soil phenomena in the study area, including some of a significant order referring to the association between "humidity threat" and soil organic matter variables for the analyzed plant covers.